DETERMINING THE EFFECTS OF POLLUTANTS ON SOME TYPES OF MICRO ALGAE AND MYTILUS GALLOPROVINCIALIS (LAMARCK, 1819) - Yüce, Arzu Morkoyunlu (International Journal of Research -GRANTHAALAYAH, 2020)
This study was conducted to determine the effects of aquatic pollutants on aquatic organisms. Izmit Bay, which is polluted both domestically and industrially, was chosen as the study area. Densely populated areas and industry are located around the Izmıt Bay. For this purpose, mussel and micro algae samples were taken from selected stations. In the study, salinity value was measured in the range of 22% - 28%. Water temperature, pH and conductivity varied from 9.20 – 25.01 ℃, 6.81 - 8.3, 30.42 - 45.11 µS/cm, dissolved oxygen values as minimum and maximum 4.62 – 12.61 mg l−1 were determined respectively. In heavy metal analyses Al, Mn, Zn, Cu, Pb, Cr, Ni, Cd and Fe) of seawater were determined in the study. As a result of the study, the highest heavy metal ratio in Mytilus galloprovincialis was determined to be iron. In the study, Oscilatoria sp., Ulnaria sp. and Nitzschia sp. taxa were determined as dominant. These species have high tolerance to aquatic pollution parameters.